Pengaruh kemajuan teknologi terhadap perlindungan hak asasi manusia - Wardana, Yunanrara Deka (Maliki Interdisciplinary Journal, 2026)
Rapid technological progress has changed many aspects of human life in a short period of time. Digital technology, including the internet and social media, has made communication, information access, and daily activities easier for society. However, along with these advantages, technological development also creates new concerns related to the protection of human rights. This study aims to examine how technological advancement influences human rights protection in today’s digital environment. The writing method uses a descriptive approach supported by literature review from sources discussing technology, law, and social life. The study findings indicate that technological growth gives both beneficial and challenging effects on human rights protection. On the positive side, technology helps people gain wider educational access, express opinions more freely, and obtain information quickly. Digital platforms also provide opportunities for individuals and communities to raise social awareness and support justice issues. On the other hand, the expansion of technology may lead to problems such as misuse of personal information, online bullying, false information distribution, excessive digital monitoring, and possible limitations on freedom of expression. These conditions show that technological use needs balanced legal protection, ethical responsibility, and stronger public awareness to maintain human rights within the digital sphere.